An historical perspective of income tax legislation in South Africa, 1910 to 1925 - Surtees, Peter Geoffrey (Rhodes University, Faculty of Commerce, Department of Accounting, 1986)
From Introduction: This work considers the period from Union, 31 May 1910 until promulgation of the Income Tax Act No. 40 of 1925.(1) It will describe the means, both financial and otherwise, by which the fledgling Government of the Union of South Africa contrived to balance its budget, and will consider the various sources of revenue available up to 1914, when the Government of Gen. Louis Botha first decided that a tax on income was necessary in order to maintain the solvency of the new State. Similarly the political pressures which shaped the nature of the Income Tax Acts up to 1925 will be discussed, and the political principles (or expediencies, depending on the degree of cynicism of the reader) which led the parties in power from time to time to make the decisions they did regarding the provisions of the various Acts. The effect of external political situations such as the Great War of 1914 - 1918 will be examined, as will the consequences of the rebellion of 1914 and the strikes of 1913 and 1922. The legislation predictably spawned a considerable body of litigation as taxpayers hastened to find and exploit loopholes in it; the resultant Income Tax Cases, in the Income Tax Special Court, Supreme Court and Appeal Court, formed the embryo of a body of judicial precedent which today encompasses some two thousand case reports. A few of the cases decided in the period up to 1925 are still quoted today; for example, CIR v Lunnon 1924 AD 1 SATC 7. The relevant cases from the period will enjoy consideration, with descriptions of how their verdicts affected either subsequent income tax principles or later legislation. Also considered will be the inception during this period of the way in which income tax legislation largely develops: the legislature promulgates an Act, the taxpayers discover legitimate ways to reduce their tax burden and the Minister of Finance consequently causes the Act to be changed in order to protect the tax base. Thereupon the resolute taxpayers seek loopholes anew. The effect of economic conditions on income tax legislation will engage attention; several such conditions cast their shadows into the House of Assembly during that 15 year period, notably the post-war recession and the drought of 1919. The selection of this period is apposite for several reasons: it covers the period during which income tax legislation came into being; - it includes several notable political occurrences. thus making possible a consideration of their effect on income tax legislation; it includes a natural cataclysm. namely a major drought. which also had an effect on subsequent Income Tax Acts; - a sufficient number of income tax cases was heard during the period to afford a fair indication both of how the body of case law would develop and how it would perpetually interplay with the legislation; it clearly illustrates the differences between the two great political parties of the time, differences largely caused by the vested interests of each; the dominant South African Party, with its need to retain the support of the commercial and particularly the mining sectors, and the smaller but even then growing National Party with its face set firmly towards the rural constituencies and the embattled farmers; - the period culminates in the Income Tax Act of 1925, a significant change from its predecessors, and the second Income Tax Act of the Pact Government. The imposition of taxes by the respective provinces does not form part of this work, as the scope of the discussion is limited to the various Income Tax Acts, and their development has been overseen by the central government.
Keywords: Income tax -- South Africa; Income tax -- Law and legislation -- South Africa; Income tax -- South Africa -- History